2010
DOI: 10.4012/dmj.2009-019
|View full text |Cite
|
Sign up to set email alerts
|

Surface texture and roughness of polished nanofill and nanohybrid resin composites

Abstract: Nanofiller-containing resin composites have gained appreciable market share in dentistry due to their claims of high mechanical strength and low polymerization contraction. In this study, the polishability of one nanofill (Filtek Supreme XT/FIL) and three nanohybrid materials (Grandio/GRA, Tetric EvoCeram/TET, Venus Diamond/VED) was investigated using surface profilometry and SEM. After the specimens were cured under a Mylar strip or pre-ground with 600-grit SiC paper, three polishing systems were applied and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 32 publications
(39 reference statements)
8
88
1
6
Order By: Relevance
“…5b and 6b), on which Enhance/PoGo created a smoother surface topography than Venus Supra. Similarly, Endo et al 17) and Jung et al 18) described detrimental surface alteration effect of relatively large diamond particles in finishing instruments on resin composites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5b and 6b), on which Enhance/PoGo created a smoother surface topography than Venus Supra. Similarly, Endo et al 17) and Jung et al 18) described detrimental surface alteration effect of relatively large diamond particles in finishing instruments on resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from traditional hybrid and micro-hybrid composites, nano-fill and nano-hybrid composites represent the state of the art in terms of filler formulation 19) . Regarding surface roughness after polishing, nano-hybrids may not perform like nanofilled composites 17,21) , but their performance is similar to or slightly better than that of micro-hybrids 21) . To our knowledge, there is no comparison in the literature of surface roughness among the micro-hybrid, nanohybrid and supra-nanofilled composites polished with two-step polishing systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difference in the degree of hardness influenced the effectiveness or the action of polishing instrument. 5,9 Sen et al 9 in his research stated that bisacryl composite had a smoother surface if polished using diamond paste compared to aluminum oxide. In this research, aluminum oxide had a lower effectivity compared to diamond particle for polishing composite nanofill.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Jung et al 13 with Tetric EvoCeram (Ivoclar Vivadent), conducted a research on the surface toughness of 3 nanofill composites and one nanohybrid composite after polishing. The result from the research showed that there was one composite nanofill possessed a higher surface toughness compared to nanohybrid.…”
Section: Discussionmentioning
confidence: 99%